Unbalance Between Sarcoplasmic Reticulum Ca2 + Uptake and Release: A First Step Toward Ca2 + Triggered Arrhythmias and Cardiac Damage - Federico, Marilén; Valverde, Carlos A.; Mattiazzi, Alicia; Palomeque, Julieta (Frontiers in Physiology, 2020)
The present review focusses on the regulation and interplay of cardiac SR Ca2+ handling proteins involved in SR Ca2+ uptake and release, i.e. SERCa2/PLN and RyR2. Both RyR2 and SERCA2a/PLN are highly regulated by post-translational modifications and/or different partners’ proteins. These control mechanisms guarantee a precise equilibrium between SR Ca2+ reuptake and release. The review then discusses how disruption of this balance alters SR Ca2+ handling and may constitute a first step towards cardiac damage and malignant arrhythmias. In the last part of the review, this concept is exemplified in different cardiac diseases, like prediabetic and diabetic cardiomyopathy, digitalis intoxication and ischemia-reperfusion injury.